1987
DOI: 10.1161/01.atv.7.5.441
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil inhibits development of atherosclerosis in rhesus monkeys.

Abstract: The effect of feeding fish oil (Menhaden) on the progression of rhesus monkey atherosclerosis was determined by feeding diets containing 2% cholesterol and either 25% coconut oil (Group I), 25% fish oil/coconut oil (1:1) (Group II), or 25% fish oil/coconut oil (3:1) (Group III) for 12 months (n = 8/group). The average serum cholesterol levels were 875 mg/dl for Group I, 463 mg/dl for Group II, and 405 mg/dl for Group III. HDL cholesterol levels were 49 mg/dl for Group I, 29 mg/dl for Group II, and 20 mg/dl for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
3

Year Published

1988
1988
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(58 citation statements)
references
References 34 publications
2
53
0
3
Order By: Relevance
“…Several studies in experimental animals have also shown that n-3 PUFA-enriched diets decrease the extent of dietinduced atherosclerosis (17,(34)(35)(36). Diets enriched in fish oil containing the n-3 PUFA, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) had a protective effect similar to or better than n-6 PUFA, as reported in nonhuman primates (17).…”
Section: Reduction Of Oleate Enrichment In Plasmamentioning
confidence: 79%
“…Several studies in experimental animals have also shown that n-3 PUFA-enriched diets decrease the extent of dietinduced atherosclerosis (17,(34)(35)(36). Diets enriched in fish oil containing the n-3 PUFA, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) had a protective effect similar to or better than n-6 PUFA, as reported in nonhuman primates (17).…”
Section: Reduction Of Oleate Enrichment In Plasmamentioning
confidence: 79%
“…In rhesus monkeys fed either fish-oil cholesterol or cholesterol diets, the fish-oil group has reductions in serum cholesterol, aortic intimal atherosderosis, and atherosderotic plaque size. 51 Similarly, the cynomolgus monkey on a hypercholesterolemic diet supplemented with fish-oil shows reduction in severity of atherosclerosis in the aorta, coronary, and common carotid artery; however, the carotid bifurcation has more severe atherosderosis. 52 Also, Japanese quail fed a hypercholesterolemic diet and supplemented with fish-oil have reduced serum cholesterol and no early genesis of coronary artery atherosderosis.…”
Section: Discussionmentioning
confidence: 99%
“…The health implication of an increased n-3 VLCPUFA intake is therefore not unequivocal. The diverging results of trials in which animals were fed n-3 VLCPUFA further underscore this uncertainty (Weiner et al, 1986;Davis et al, 1987;Fincham et al, 1991;Barbeau et al, 1997). Accordingly, it is still a controversial issue whether ®sh protects against CHD.…”
Section: Introductionmentioning
confidence: 99%